2005
DOI: 10.1007/11539087_163
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Structured Feedforward Neural Networks to the Modelling of the Daily Series of Currency in Circulation

Abstract: The Working Paper Series of the Czech National Bank (CNB) is intended to disseminate the results of the CNB's research projects as well as the other research activities of both the staff of the CNB and collaborating outside contributors. The Series aims to present original research contributions relevant to central banks. It is refereed internationally. The referee process is managed by the CNB Research Department. The working papers are circulated to stimulate discussion. The views expressed are those of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…The suggested neural network's forecasting abilities were contrasted with those of the conventional ARIMA model. The results show that neural networks perform better than ARIMA models, and both models may be used, at the very least as auxiliary tools for forecasting liquidity (Hlavacek, Konak, and Cada, 2005). Three models linear forecasting, regression, and seasonal ARIMA models were used to estimate and predict the daily and weekly CIC for the state of Qatar.…”
Section: Empirical Review Of Literaturementioning
confidence: 99%
“…The suggested neural network's forecasting abilities were contrasted with those of the conventional ARIMA model. The results show that neural networks perform better than ARIMA models, and both models may be used, at the very least as auxiliary tools for forecasting liquidity (Hlavacek, Konak, and Cada, 2005). Three models linear forecasting, regression, and seasonal ARIMA models were used to estimate and predict the daily and weekly CIC for the state of Qatar.…”
Section: Empirical Review Of Literaturementioning
confidence: 99%
“…The integrated ARMA model has been used extensively for the non‐stationary time series. To our best knowledge, recent central bank research papers including Cabrero et al (2002), Hlavàcek et al (2005) and Basac et al (2006) used the seasonal ARIMA models and obtained accurate estimations for the CIC.…”
Section: Empirical Modelsmentioning
confidence: 99%
“…Cabrero et al (2002) noted that the error in forecasting banknotes in circulation never exceeds €1 billion in either models mentioned above and they concluded that econometric models are able to explain an important part of the variation in the currencies in the circulation. Hlavàcek et al (2005) forecasted the CIC for Czech Republic using both linear (ARIMA) and non‐linear techniques. Their study provided satisfactory forecasts using the ARIMA models both for long‐term and short‐term horizons[3].…”
Section: Introductionmentioning
confidence: 99%